TRACING THE EVOLUTION OF SUSTAINABILITY ACCOUNTING: A SYSTEMATIC LITERATURE REVIEW - Setianingsih; Ika Hardila; Rika Norarita; Dian Widiyati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to identify and analyze various factors that affect sustainability accounting through the Systematic Literature Review (SLR) approach using the PRISMA method. Sustainability accounting is increasingly important in modern business practices due to the increasing demands on transparency and social and environmental responsibility. The study examined ten scientific articles published between 2019–2025 and met inclusion criteria based on topics, methodologies, and relevance to the application of sustainability accounting. The results of the study show that some of the main factors that influence the implementation of sustainability accounting include intellectual capital, technology support, organizational culture, local cultural values, stakeholder engagement, accounting information systems, reporting standards such as GRI and IFRS, and government regulations. These findings reinforce the view that the successful implementation of sustainability accounting is highly dependent on the synergy between internal and external factors of the organization. This research contributes to academics and practitioners in understanding the dynamics and challenges of sustainability accounting, and recommends the need for institutional support, managerial capacity building, and the use of technology for more transparent and accountable reporting.